Development of Program to Support Self-Care Behavior for Blood Sugar Control among Type 2 Diabetes Mellitus Patients - Hakum, Duangtida; Chaipichit, Natapohn (Health Science, Science and Technology Reviews, 2020)
This study aimed to develop a program for blood sugar control in Type 2 Diabetes Mellitus (DM) patients who received their medications at Angthong Hospital 2. A multidisciplinary healthcare team developed group activity programs designed to counsel patients about self-care behaviors to control blood sugar. Patients’ clinical outcomes and behaviors were evaluated at 3 months after program initiation. Data were collected from 65 uncontrolled Type 2 DM patients between January and March 2019. After program initiation, significant improvement in mean behavior scores were observed in food intake (before 1.94±0.23 vs. after 2.87±0.20), exercise (before 1.96±0.27 vs. after 2.91±0.21), and medication intake (before 2.03±0.19 vs. after 2.94±0.13) (all p-value < 0.001). Significant reductions in mean HbA1C (before 7.42±0.27% vs. after 6.49±0.37%) and mean Fasting Blood Glucose (FBG before 165.55±0.25 mg/dl vs. after 115.98±0.15mg/dl) were also found (all p-value < 0.001). Medication use was monitored for all patients. More than 80% of patients showed up at each follow-up visit. This study demonstrates that the program developed here for blood sugar control successfully supported patients in improving self-care health behaviors which yielded better control of blood glucose in their therapeutic goals.